A randomized controlled trial of an educational intervention on Hellenic nursing staff's knowledge and attitudes on cancer pain management - Papathanassoglou, Elizabeth; Patiraki, Elisabeth; Tafas, Cheryl (My University, 2006)
The purpose of this randomized controlled study was to explore the effectiveness of an educational intervention on nurses' attitudes and knowledge regarding pain management and to explore associations with nurses' characteristics. A four Solomon group experimental design was employed to assess the effect of the intervention and potential effects of pre-intervention testing. One hundred and twelve nurses were randomized to two intervention and two control groups. The intervention was based on viewing a series of educational videotapes and case scenarios. The Validated Hellenic version of the Nurses Knowledge and Attitudes Survey Regarding Pain (GV-NKASRP) was used. Pre-intervention scores revealed various limitations in regard to pain assessment and management. At the pre-test, the average number of correct answers was 17.58±7.58 (45.1%±19.3% of total questions). Pre-intervention scores differed significantly among participants with different educational backgrounds (P < 0.0001). A significant effect of pain education on total knowledge scores as well as regarding specific questions was detected. Intervention group participants provided 6.11±5.55 additional correct answers (15.66%±14.23% improvement, P < 0.0001), and they exhibited significantly improved post-test scores compared to controls (26.49±5.24 vs. 18.75±4.48; P < 0.0001). A potential negative effect of pre-test on knowledge gain for specific items and for total scores was detected. These findings suggest low pre-test knowledge scores among Hellenic oncology nurses and a significant effect of the intervention
Keywords: Cancer--Nursing; Cancer pain; Greece; Pain measurement; Nurses; Nurses--Attitudes